Southern partners - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
With a great deal of political support behind the notion of South-South cooperation and the exchange of agricultural and related skills and knowledge between regions and countries, it is no wonder that there are many programmes to make this...